A Multi-layer Representation Model for the ISO/IEC 33000 Assessment Framework: Analysing Composition and Behaviour - Fernández Del Carpio, Alvaro (2017)
Software Process Improvement (SPI) models are a very important topic for SPI workers as software engineering students that require a good comprehension of the process assessment models. This paper proposes a visual multi-layered representational model describing in a highly practical way the ISO/IEC 33000 Assessment Framework through of structural and behavioural views. This kind of representation comprises several semantic layers based on the dimensions of the key elements of the model with an additional dimension for specifying measurements. The structural elements of the model are assigned on distinct layers and connected through dependence and co-occurrence connector in applying the Assessment Model on software processes. The representation model was tested with software developers, academic experts and students.